Morphological Study of the Posterior Tibial Nerve in Tarsal Tunnel of the Human Foot - Khalid, Musa Fadlelmula Awadelseid (International Journal of Human Anatomy, 2020)
The passage of the posterior tibial nerve in the tarsal tunnel has a great clinical significance, thus detailed anatomical knowledge is mandatory for safe clinical intervention. This study was to identify the morphological appearance of the tibial nerve and its bifurcation. Sixty lower limbs of formalin embalmed cadavers were randomly selected. Data were collected through the application of standard dissection method of the tarsal tunnel of lower limbs (30 rights and 30 left) of formalin embalmed cadavers. The posterior tibial nerve and its branches were exposed from the distal end of the leg toward plantar surface beyond its bifurcation by resecting the skin and flexor retinaculum. The study triggered several findings: The posterior tibial nerve is flattened shaped in 21 specimens 70% and has a rounded shape in 9 specimens 30%in the right foot. In the left foot it is flattened in 17 specimens 56.7% and rounded shape in 13 specimens 43.3%. Posterior tibial nerve bifurcates into medial and lateral planter nerves inside tarsal tunnel in 20 specimens 66.7% in the right foot and in 21 specimens 70% in the left foot. This study concludes that posterior tibial nerve commonly has flattened shape and divided into medial and lateral planter nerves inside tarsal tunnel.
Keywords: Anatomy; Dissection; Posterior tibial nerve; Tarsal tunnel; Foot.